Beberapa Faktor yang Memengaruhi Tingkat Kemiskinan di Provinsi Bali - Mega Putri, Ida Ayu Putu Septyana; Yuliarmi, Ni Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 10, Oktober 2013 (pp. 434-491), 2013)
Poverty is a complex issue in national and regional levels, so the right strategy and required sustained in anticipation of this. The purpose of this research is to know the influence economic growth, the minimum wage, education level and the level of unemployment and partial simultan against poverty of Bali period 2007-2011. This research was conducted in the whole district/city of bali, by using secondary data, method of data collection using the technique of non observation of behavior. Analytical techniques used are multiple linear regression. Based on the results of analysis found that economic growth, the minimum wage, education level and the level of unemployment simultaneously influence significantly to poverty level. The growth of the economy, the minimum wage, and level of education partially negative and significant effect on poverty levels. While the unemployment rate is partially positive but not significant effect of level of poverty.To lower the level of poverty required equitable allocation of investment income inequality so that district/city can be resolved. Minimum wages should be adjusted to the level of inflation that occurs, because if there is a need for good labor price inflation, spending also increased. Exempting tuition fees of any kind, not just school fees, cost of life should also be borne. Expansion of employment oppurtunities that are labor intensive.
Keywords: poverty , economic growth , minimum wage , education level , unemployment levels